Familial Congenital Facial Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Three males with congenital facial palsy from 3 generations in the same family are reported from the Floating Hospital for Children, Tufts-New England Medical Center, Boston, MA.